Ethanol with thioacetamide murine model of alcoholic liver disease identifies hepatic pathways as targets for the human disease - Ashi Mittal; Nishu Choudhary; Sudrishti Chaudhary; Anupama Kumari; Archana Rastogi; Guresh Kumar; Jaswinder Singh Maras; Shiv K Sarin; Shvetank Sharma (Annals of Hepatology)
Introduction and Objectives: Hepatic proteome and gut microbiota alterations are known in alcohol-associated hepatitis (AAH). Current animal models sparsely mimic human AAH. We aimed to develop an murine model that closely resembled human AAH. Materials and Methods: Male C57BL/6N mice were pair-fed control/incremental ethanol Lieber-DeCarli diets and thioacetamide (TAA) for 12-weeks to induce AAH. Hepatic proteome was analyzed using LC-MS/MS. Gut-bacteria was determined using 16s-rRNA sequencing. Results: Mice exposed to EtOH+TAA displayed higher expression of liver triglycerides (1.5-fold, p = 0.001), pro-inflammatory (IL6, 1.5-fold, p = 0.002 and TNFα, 1.7-fold, p = 0.01), fibrotic (TGF-β, 2.7-fold, p = 0.01 and Col1α1, 2-fold, p = 0.01) and oxidative markers (GSH and SOD (-1.5 fold, p = 0.004 & 0.005 respectively)) as compared to EtOH alone. Histology of EtOH+TAA liver displayed pericellular liver fibrosis, increased steatosis, and neutrophil infiltration, which resembled human AAH. In the 12wk EtOH+TAA group, Desulfobacteria, Campylobacteria, and Patescibacteria increased by 2-fold (p = 0.02). Pathway combined score (CS, log10) in EtOH+TAA treatment showed upregulated hepatic ethanol oxidation (CS=1.93), fatty acid biosynthesis (CS=2.48), necrosis (CS=1.59), collagen formation (CS=1.28) and hypoxia (CS=0.68) and downregulated fatty acid beta-oxidation (CS=2.37), PPAR signaling (CS=1.35) fatty acid degradation (CS=2.35), bile acid metabolism (CS=1.87), and oxidative phosphorylation (CS=1.50), as observed in human disease. Conclusions: Using an ethanol-thioacetamide combination in mice results in a faster establishment of AAH with fibrosis than previously known models. Differential protein expression strongly correlates with pathways found altered in human AAH, thus making the model mimic human disease better than other known models., respectively. Thioacetamide (TAA) was administered to enhance liver fibrosis and mimic human AAH.